THE RELATIONSHIP BETWEEN ENTREPRENEURSHIP KNOWLEDGE AND ENTREPRENEURIAL INTENTION IN CHEMISTRY EDUCATION STUDENTS - Iklima Syukriah; Burhanudin Milama (STMIK Indonesia Banda Aceh, 2026)
The high unemployment rate among college graduates indicates that higher education has not yet been fully successful in preparing graduates to be economically independent. One of the efforts undertaken by universities is through entrepreneurship education, which is expected to foster students’ entrepreneurial intentions. This study aims to analyze the relationship between entrepreneurial knowledge and entrepreneurial intentions among Chemistry Education students at UIN Syarif Hidayatullah Jakarta, both those who have and those who have not taken entrepreneurship courses. The study employed a quantitative approach using a correlational method. Data were collected through a survey using a questionnaire administered to 78 students from the 2021–2025 cohorts, selected via proportional stratified random sampling. Data analysis was conducted using Spearman’s rank correlation. The results indicate a positive and significant relationship between entrepreneurial knowledge and entrepreneurial intention, both among students who have taken the entrepreneurship course and those who have not, with a stronger relationship observed among students who have taken the course. These findings underscore the importance of formal entrepreneurship education in strengthening students’ entrepreneurial intention, particularly within science-based programs.